Climate-Responsive Environmental Monitoring in Sustainable Management of Air Quality and Pollution - Hoang, Anh The; Dau, Khac Tai; Tran, Dinh Du; Tran, Hau Thin (Dr. Viktor Koval, 2026)
Background. Air pollution is a significant threat to human health and the global environment. In the context of climate change, air pollution is becoming increasingly severe and challenging to control. In regions with harsh climates, such as Nghe An Province (Vietnam), controlling air pollution becomes even more difficult. Climate change has accelerated the formation of ozone (O3), prolonged the retention time of pollutants in the air, and increased the risk of forest fires, leading to the dispersion of particulate matter and other impacts. Appropriate air quality management measures are necessary to ensure that the air environment of Nghe An Province meets national standards. Purpose. This study aims to examine the current level of air pollution in Nghe An Province by analysing monitoring data and air quality management policies. The air quality monitoring data will be compared with Vietnam’s National Technical Regulation on Air Quality (QCVN 05:2023/BTNMT) to assess the pollution status. The study also proposes sustainable air quality management solutions tailored to climate change in Nghe An Province, addressing both the short-term and long-term implications. Findings. The study used data from 119 air quality monitoring points across Nghe An Province, with areas including rural, urban, industrial, construction, mining, landfill, traffic, and tourist areas. An analysis of the concentrations of pollutants such as SO2, CO, NO2, and Total Suspended Particulates (TSP) showed that Nghe An’s air quality was good, with most indicators remaining within the safe limits prescribed by QCVN 05:2023/BTNMT. However, some monitoring points recorded values that exceeded the permissible threshold. Of the 119 monitoring points, seven exceeded the limit for TSP (accounting for 5.9%). The TSP concentration fluctuated from 111 µg/Nm3 to 432 µg/Nm3 during the study period. Although the province has directed efforts toward air quality management, several bottlenecks remain, including the limited application of modern technology and the inadequate management of agricultural waste burning. To ensure sustainable development under climate change, several air quality management measures have been proposed for Nghe An Province to improve air quality. Implications. The air environment faces challenges as climate change significantly impacts environmental pollution. An analysis of air quality monitoring data from 119 stations across Nghe An Province indicated that the air quality was generally good, with only 5.9% of the stations reporting TSP concentrations that exceeded national standards. Although the current air quality in Nghe An Province is within safe limits, appropriate management solutions are necessary to ensure the health and safety of the local population and to guarantee sustainable development.